Performing Purity: Slut Shaming and Gendered Communication in Indonesian Cancel Culture - Fadila Rahma Sari; Anang Sujoko; Fitri Hariana Oktaviani (Mediator: Jurnal Komunikasi, 2025)
This study examines how slut-shaming operates within Indonesian cancel culture, focusing on the 2022 scandal involving actress Arawinda. Infidelity scandals were selected because they consistently attract massive online engagement in Indonesia and function as forms of collective entertainment that invite moral judgment. Cancel culture is often portrayed as a practice of accountability, but it reproduces gendered power relations by disproportionately targeting women. This study analysed how X discourse positioned women as the primary bearers of blame while minimising or erasing men’s responsibility. More than 2.000 tweets were collected using Selenium-based scraping, from which 633 tweets containing slut-shaming discourse were purposively sampled and analysed through a qualitative critical paradigm. Feminist Poststructuralist Discourse Analysis (FPDA) was applied to examine how sexualized language and moral judgments construct gendered subjectivities. The findings show that digital spaces do not serve as neutral arenas of accountability, but instead reinforce patriarchal norms and gender inequalities.